(untitled) (Clinics, 2013)
Previous studies have investigated the effects of auditory temporal training on language disorders. Recently, the effects of new approaches, such as musical training and the use of software, have also been considered. To investigate the effects of different auditory temporal training approaches on language skills, we reviewed the available literature on musical training, the use of software and formal auditory training by searching the SciELO, MEDLINE, LILACS-BIREME and EMBASE databases. Study Design: Systematic review. Results: Using evidence levels I and II as the criteria, 29 of the 523 papers found were deemed relevant to one of the topics (use of software - 13 papers; formal auditory training - six papers; and musical training - 10 papers). Of the three approaches, studies that investigated the use of software and musical training had the highest levels of evidence; however, these studies also raised concerns about the hypothesized relationship between auditory temporal processing and language. Future studies are necessary to investigate the actual contribution of these three types of auditory temporal training to language skills.